2008
DOI: 10.5194/angeo-26-671-2008
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Birkeland current distributions from magnetic field observations by the Iridium constellation

Abstract: Abstract. We present a statistical analysis of Birkeland currents derived from Iridium magnetometer data acquired in the Northern Hemisphere to determine the dependence of large-scale currents on the interplanetary magnetic field (IMF) direction. Because the Iridium data span nearly seven years, we can restrict analysis to only those intervals with stable currents. We used image comparison to quantify the consistency between successive one-hour current distributions and selected 1550 two-hour intervals, 5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

46
196
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(243 citation statements)
references
References 31 publications
(54 reference statements)
46
196
1
Order By: Relevance
“…A distinct pair of oppositely directed FACs was present at the migrating flow channel as observed by Defense Meteorological Satellite Program (DMSP) F13 and F15 which is consistent with the electrodynamic scenario envisioned by Southwood [1987] and the inferred ExB flow proposed by Anderson et al [2008]. The observed link between the flow channel in the ionosphere and the IMF clock angle is in qualitative agreement with a highlatitude reconfiguration of a reconnection region [Luhmann et al, 1984].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…A distinct pair of oppositely directed FACs was present at the migrating flow channel as observed by Defense Meteorological Satellite Program (DMSP) F13 and F15 which is consistent with the electrodynamic scenario envisioned by Southwood [1987] and the inferred ExB flow proposed by Anderson et al [2008]. The observed link between the flow channel in the ionosphere and the IMF clock angle is in qualitative agreement with a highlatitude reconfiguration of a reconnection region [Luhmann et al, 1984].…”
Section: Introductionsupporting
confidence: 74%
“…The FAC maps demonstrate that the most high-latitude pair of opposite FACs rotates in a statistical sense with the IMF By/Bz clock angle for northward and neutral IMF Bz. Anderson et al [2008] inferred a corresponding ExB flow between the oppositely directed FACs. The proposed flow is azimuthally directed toward the northern dusk (dawn) for negative (positive) IMF By with opposite flow directions expected in the Southern Hemisphere (SH) for the same IMF By.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They extended the results of Weimer (2001) by investigating the hemispheric dependence of the FAC distribution and the ground state (IMF ∼0) patterns. Anderson et al (2008) presented average FAC maps for the Northern Hemisphere derived from magnetic field observations obtained from the Iridium satellite constellation. The average Northern Hemisphere, Iridium FAC maps for southward IMF and the model results presented by Papitashvili et al (2002) for Northern Hemisphere summer showed broad agreement.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a large-scale FAC system (also known as Birkeland currents), which includes the Region 1 FAC that couple the external magnetosphere current to the high-latitude ionosphere and the Region 2 FAC that couple the inner magnetosphere to the auroral ionosphere. These large-scale current systems have been widely reported and documented in statistical work using single spacecraft [e.g., Iijima and Potemra, 1976] and satellite constellations [Anderson et al, 2008]. More recently, near-instantaneous global distributions of the FACs have been inferred by the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE) [Anderson et al, 2014].…”
mentioning
confidence: 99%